2019
DOI: 10.1016/j.jpeds.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Incidence, Duration, and Return to School and Sport in 5- to 14-Year-Old American Football Athletes

Abstract: Objective To collect prospective data on concussion incidence, risk factors, duration of symptoms, and return to school and sport in 5-to 14-year-old American football participants. Study design We conducted a prospective cohort study over 2 years collecting data during two 10-week fall seasons. Youth with concussion were followed to determine time to return to school, sport, and baseline level of symptoms. Logistic regression was used to estimate the risk of sustaining a concussion associated with baseline de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Based on survey results, 61% of concussed participants self-reported academic dysfunction 1 month after their injuries [ 20 ]. In another prospective study, Chrisman et al reported that 90% of participants returned to the school environment by 9 days with the mean days until return reported as 6.7 days [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on survey results, 61% of concussed participants self-reported academic dysfunction 1 month after their injuries [ 20 ]. In another prospective study, Chrisman et al reported that 90% of participants returned to the school environment by 9 days with the mean days until return reported as 6.7 days [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used numerical measures to assess academic decline following SRC, while other studies used subjective methods such as surveys assessing adolescent or parent perspectives on academic challenges experienced while returning to school post-concussion [ 10 , 11 , 14 , 15 , 16 , 17 , 18 ]. Of the studies that reported survey-based data on adolescent or parent perspectives, all reported a significant level of concern with respect to academic difficulty [ 7 , 12 , 13 , 19 , 20 , 21 ]. While this data is not quantitative, it highlights the need for further research, as self-reported measures of executive dysfunction have shown to be strong predictors of academic dysfunction [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both male and female athletes and all ages (6-18 years) were included in the analysis because non-tackle football is played by both sexes and these ages. We acknowledge that sex and age may influence the injury risk, 4,23,36 but we were unable to parse out data by either, as some estimates were rendered unstable because of too few cases. Thus, we cannot postulate whether significant differences across sports in these demographic factors reflect underlying differences in participation or demographic-specific injury risks.…”
Section: Discussionmentioning
confidence: 99%
“…Concussion or mTBI-related injuries have been a growing issue, both in adults and youths. [56][57][58][59] While return to baseline after 3 weeks is common in individuals aged 5-14 years, 58 post-concussion syndrome (concussion-like symptoms lasting over 3 months following mTBI) has been shown to persist for over 6 months in 40% of mTBI patients. 60 Post-concussion syndrome can have negative effects on the individual's day-today activities, as shown through its negative associations with health-related quality of life, assessed by the 36-item Short-Form Health Survey and Perceived Quality of Life Scale.…”
Section: Concussion Implication and Endocannabinoid Neurophysiology Imentioning
confidence: 99%